Nutrient Condition of Kampar Big River Estuary: Distribution of N and P Concentrations Drifted by Tidal Bore ”Bono” - Ulung Jantama Wisha; Lilik Maslukah (Marine Science Department Diponegoro University, 2017)
Due to accelerated anthropogenic activity, a significant amount of pollutants has been directly or indirectly discharged into coastal estuaries of Kampar. Nutrient pollution along the river to the estuary that adversely affects coastal and estuary ecosystem mainly originates from inland such as industrial effluent, household, and agricultural waste as well as a naturally derived pollutant from biogeochemical cycle, which is controlled by the propagation of undular bore (Bono). The purpose of this study is to determine the environmental impact of distribution of nutrients caused by the mechanism of Bono. This research employed a purposive quantitative method, the concentration of dissolved phosphate, nitrate, nitrite and ammonia was analyzed using a spectrophotometer, tidal data retrieval was measured for 30 days’ near the estuarine area, while, current flow was measured for 24 hours’ measurement. Phosphate concentrations ranged from 0.02-0.1 mg.L-1, nitrate concentrations ranged from 0.76-5.73 mg.L-1, ammonia concentrations ranged from 0.2-0.41 mg.L-1, nitrate concentrations ranged from 0.001-0.03 mg.L-1. The tidal type is mixed tide prevailing semidiurnal with tidal range reach 4.2 m during spring tide condition. At the time of Bono propagate, drastically enhance the surface elevation and directly increase the drift of velocity with the flow direction from estuary into the river upstream, that mechanism affects the nutrient distribution in Kampar river. Keywords: Bono, Fluid dynamics, Nutrient distribution, Tidal bore, Water quality